The status of spotted seatrout (Cynoscion nebulosus) as a technologically feasible species for U.S. marine aquaculture - Reginald Blaylock; Eric Saillant; Angelos Apeitos; David Abrego; Paul Cason; Robert Vega (Wiley, 2025)
Culture models and facilities for large-scale, commercial production of popular Gulf of Mexico species are unavailable. The spotted seatrout (Cynoscion nebulosus) is one of the most popular recreational fishes in the Gulf of Mexico. Seatrout culture techniques were adapted from red drum (Sciaenops ocellatus) protocols developed in the 1970s. Broodstock husbandry, spawning, and extensive pond rearing techniques using fertilized and bloomed brackish ponds were well-established by the 1980s. By 2018, approximately 80 million 25–30-day old seatrout had been produced, mainly for stock enhancement. Cannibalism and poor nutrition hindered intensive tank culture. Between 2005 and 2015, an intensive tank-rearing protocol that reduced cannibalism and intracohort variability and increased average survival to almost 50% was developed using algal concentrate, rotifers, brine shrimp (Artemia sp.), and microencapsulated feeds. Preliminary results suggested that a 500 g fish could be produced in approximately 10 months. Nevertheless, interest in commercialization has remained low. Zootechnical performance throughout the latter stages of culture, the economics of production, consumer preferences/perceptions, and market capacity must be documented to complete the assessment of the spotted seatrout as a species for commercial aquaculture. The optimization of aquafeeds specific for seatrout and a domestication program is warranted to further facilitate industry growth.